2019
DOI: 10.21009/biosferjpb.v12n1.109-121
|View full text |Cite
|
Sign up to set email alerts
|

Developing students' worksheet based on scientific approach in cell as the system of life

Abstract: Students worksheet scientific approach is a teaching material that contains material that teaches students to experiment by following the steps based on the scientific method. The scientific method is observed, ask, gather information, associate, and communicate. The results of observation, interview with the teachers and students found that the teacher uses the revised version of the 2013 Curriculum’s handbook of natural science for grade VII. The books contain student activities cannot be done because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Marjan, Arnyana, & Setiawan, (2014), stated that scientific approach learning was better than the direct learning model in improving learning result of biology and scientific process skill. Subamia, Wahyuni, & Widiasih, (2014), stated that equipment of experiment being developed had an advantage compared to the standard one, including: (1) the equipment is adjusted in accordance with the 2013 Curriculum that demands the learning of natural science in junior high school is conducted with scientific approach.…”
Section: Resultsmentioning
confidence: 99%
“…Marjan, Arnyana, & Setiawan, (2014), stated that scientific approach learning was better than the direct learning model in improving learning result of biology and scientific process skill. Subamia, Wahyuni, & Widiasih, (2014), stated that equipment of experiment being developed had an advantage compared to the standard one, including: (1) the equipment is adjusted in accordance with the 2013 Curriculum that demands the learning of natural science in junior high school is conducted with scientific approach.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative in practicing critical thinking skills in the science learning process is to use teaching materials in the form of handouts in the learning process. The user can be practical because the handout contains summaries of the material to immediately find out the essential parts of the material being studied (Fajarianingtyas, Akbar, and Herowati 2019;Prastowo 2012). The results showed that using handouts in the learning process could improve critical thinking skills and problem-solving skills (Khotimah and Hastuti 2021;Sumarni and Badruzsaufari 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The textbook which was developed based on this scientific approach is following the demands of the education curriculum in Indonesia. Like several previous studies which state that the scientific approach can fulfill the competence of the realm of knowledge and skills and is presented by the demands of the curriculum (Asrizal et al, 2018;Fajarianingtyas et al, 2019;Ibrohim, 2015;Novianto & Mustadi, 2015;Setiyadi et al, 2017). In addition, textbooks related to additives and addictive substances are supported by presentations that are coherent with the thought process through a scientific approach.…”
Section: Discussionmentioning
confidence: 91%